Two new Deltocephalini leafhopper genera (Hemiptera: Cicadellidae: Deltocephalinae) from China - Zhang, Yalin; Duan, Yani (Zootaxa, 2006)
Two new genera of Deltocephalini, Yuanamia gen. nov. with Y. anastoma sp. nov. as type species and Wyushinamia gen. nov. with W. bifurcata sp. nov. as type species, are described and illustrated from China.